Clinical profile and outcome among patients with acute-on-chronic liver failure admitted in the intensive care unit - Marwa Lotfi El Sayed; Tarek El Sayed Gouda; E. L. Sayed Abdel Maksood Khalil; Mohammed Mohammed El Sayed Al Arman; Islam Eid Mohamed (SpringerOpen, 2021)
Abstract Background Acute-on-chronic liver failure (ACLF) has been recently defined as a clinical form including acute hepatic decompensation and high 28-day mortality. ACLF usually follows a precipitating event on the background of established cirrhosis. ACLF is considered the most frequent indication for admission to the ICU among cirrhotic patients. Our research aimed to reveal the clinical profile and outcome among patients with ACLF to detect an allocation system of these patients to the intensive care unit (ICU), and a decision tool for clinical practice. It is a prospective study of 60 patients with ACLF. Patients are divided into group A that included 30 patients with ACLF admitted to the hepatology and gastroenterology ward and group B that also included 30 patients with ACLF admitted to the ICU. Each group is subdivided into subgroups regarding the grade of ACLF. Results The most common precipitating factor of ACLF is SBP 78.3% (80% in ICU, 73.6% inward). Renal failure is the most common organ failure in ACLF in both groups. CLIF-C ACLF is assumed to be a highly prognostic score for mortality in ACLF patients better than other scores. ROC curve of CLIF-C ACLF with AUC: 0.972 and CI: 0.919, 1.025 showed a cutoff point = 57.0 above which intensive care admission does not seem to benefit ACLF patients. The sensitivity at the optimal cut point is 88.89% and the specificity is 100%. There is a significant difference between the 3 ACLF groups regarding 1-month and 3-month mortalities in patients admitted to the ICU. ACLF1 shows the least 1-month and 3-month mortality rates while ACLF3 shows the highest mortality rates in ICU patients ((1-month mortality: 20%, 60%, 100% in ACLF1, 2, 3 respectively), (3-month mortality: 50%, 80%, 100% in ACLF1, 2, 3 respectively)). Conclusion Mortality is high in ACLF and increases with the number of organ failures (40% in ACLF1 to 100% in ACLF3). CLIFC-ACLF is the most prognostic scoring system with a cut-off value of 57; above this value, mortality is a fact.